Audiovisual Education Techniques on Mothers' Psychomotor Abilities in First Aid for Febrile Seizures in Toddlers - Girianto, Pria Wahyu Romadhon; Fuadah, Dina Zakiyyatul (Chakra Brahmanda Lentera Institute, 2024)
Background: One of the health issues that frequently affect infants is febrile seizures, which are brought on by a fever without any cerebral infection. This could cause death, paralysis, or even damage to the brain. This study aimed to analyze the effect of audio-visual techniques on the psychomotor abilities of mothers in providing first aid for simple febrile seizures in toddlers. Methods: The research design was a pre-experiment, a one-group pretest, and a post-test with a population of 90 mothers and a sample of 30 mothers with toddlers obtained by the purposive sampling technique. The inclusion criteria were mothers who were willing to be respondents, mothers with healthy toddlers, and mothers over 18 years of age. The pre-test was carried out before the intervention, and the intervention was given twice in one week with a duration of 25–30 minutes. A post-test was then carried out. Results: The Wilcoxon signed-rank test was used for statistical analysis (α = 0.05). The results of the study were obtained before the intervention; all respondents had psychomotor abilities in the lower category, and after the intervention, most of the respondents' psychomotor skills were in the higher category. Statistical results obtained a p-value of 0.000 (α = 0.05), which means that there was an effect of audiovisual education techniques on the psychomotor ability of the mother in first aid for simple febrile seizures. Conclusion: Audiovisual education techniques could stimulate the two senses of sight and hearing simultaneously, so that mothers were more focused on the material provided and the material was easier to accept, especially for psychomotor competence. Audiovisual techniques should be used as an alternative learning method for ordinary people because they are more effective in improving psychomotor abilities.